Advancements and challenges in CAR T cell therapy in autoimmune diseases - Schett, Georg; Müller, Fabian; Taubmann, Jule; Mackensen, Andreas; Wang, Wei; Furie, Rich A; Gold, Ralf; Haghikia, Aiden; Merkel, Peter A; Caricchio, Roberto; D'Agostino, Maria-Antonietta; Locatelli, Franco; et al. (Nature reviews. Rheumatology, 2024)
Chimeric antigen receptor (CAR) T cells are highly effective at targeting and eliminating cells of the B cell lineage. CAR T cell therapy has become a standard-of-care treatment for patients with relapsed or refractory B cell malignancies. In addition, the administration of genetically modified T cells with the capacity to deplete B cells and/or plasma cells has tremendous therapeutic potential in autoimmune diseases. In the past few years, CD19-based and B cell maturation antigen (BCMA)-based CAR T cell therapies have been applied to various B cell-mediated autoimmune diseases including systemic lupus erythematosus, idiopathic inflammatory myopathy, systemic sclerosis, neuromyelitis optica spectrum disorder, myasthenia gravis and multiple sclerosis. The scientific rationale behind this approach is that deep depletion of B cells, including autoreactive B cell clones, could restore normal immune function, referred to as an immune reset. In this Review, we discuss important aspects of CAR T cell therapy in autoimmune disease, including considerations relating to patient selection, safety, efficacy and medical management. These considerations are based on the early experiences of CAR T cell therapy in autoimmune diseases, and as the field of CAR T cell therapy in autoimmune diseases continues to rapidly evolve, these issues will remain subject to ongoing refinement and adaptation.